Charismatic Leadership in the Middle East and North Africa in the 21 st Century: Regional Specifics and Prospects for the Evolution of the Phenomenon - N. Yu. Surkov (Vestnik MGIMO-Universiteta)
The article deals with authoritarian regimes based on charismatic leadership which can be also called caesarean. It analyzes the existing caesarean regimes of the Middle East and North Africa: their nature (progressive vs. conservative), characteristic features and prospects of their evolution. To achieve this goal the author uses a synthetic analytical approach based on ideas of Max Weber and Antonio Gramshi. This approach includes analysis of a number of key factors, such as conditions for eruption of a charismatic leader (‘Caesar’), sources of legitimization, mechanisms of control and power transit, progressive or conservative nature of the regime, potential for turning the caesarean regime into a permanent one based on tradition of charismatic rule. The main conclusion of the paper is that the Middle East and North Africa are witnessing the arrival of the third generation of charismatic leaders, who will follow conservative instead of progressive agenda. On the regional scale it will bring relative stability to international relations (at least among the Arab states) while at domestic level the pressure of unresolved political, economic and social problems will be mounting resulting in a new wave of revolutions and instability in the midterm.